New species of Cladiopsocus Roesler (Psocodea: ‘Psocoptera’: Psocomorpha: Cladiopsocidae) from the Colombian Amazonia - Obando, Ranulfo González; Aldrete, Alfonso N. García; Carrejo, Nancy (Zootaxa, 2016)
Ten species of Cladiopsocus Roesler were identified among recent collections from the Colombian departments of Amazonas and Putumayo. Eight new species were found, five from Putumayo and three from Amazonas, that are here described and illustrated. C. ramulosus (Enderlein) and C. domesticus (New) were found in the Putumayo department. The number of species in the genus is increased to 28, with two from Angola, and 26 from the Neotropics. An identification key to the males of the neotropical species is included.